2015
DOI: 10.4161/15384047.2014.972264
|View full text |Cite
|
Sign up to set email alerts
|

Calcium calmodulin dependent kinase kinase 2 - a novel therapeutic target for gastric adenocarcinoma

Abstract: Gastric cancer is one of the most common gastrointestinal malignancies and is associated with poor prognosis. Exploring alterations in the proteomic landscape of gastric cancer is likely to provide potential biomarkers for early detection and molecules for targeted therapeutic intervention. Using iTRAQ-based quantitative proteomic analysis, we identified 22 proteins that were overexpressed and 17 proteins that were downregulated in gastric tumor tissues as compared to the adjacent normal tissue. Calcium/calmod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 55 publications
1
79
0
Order By: Relevance
“…Second, the other major AMPKK, CAMKKβ is not a TS gene in human cancer [136138]. In fact, CAMKKβ is overexpressed up to 7-fold in 92/98 (94%) of gastric cancer [141], and played an AMPK-mediated role in metabolic reprograming, migration and invasion in prostate and colon cancer [126,128,142,143]. It is reasonable to predict that oncogene-induced ER stress and calcium disequilibrium can activate a specific pool of the AMPK heterotrimer through CAMKKβ.…”
Section: The Many Functions Of Ampkmentioning
confidence: 99%
“…Second, the other major AMPKK, CAMKKβ is not a TS gene in human cancer [136138]. In fact, CAMKKβ is overexpressed up to 7-fold in 92/98 (94%) of gastric cancer [141], and played an AMPK-mediated role in metabolic reprograming, migration and invasion in prostate and colon cancer [126,128,142,143]. It is reasonable to predict that oncogene-induced ER stress and calcium disequilibrium can activate a specific pool of the AMPK heterotrimer through CAMKKβ.…”
Section: The Many Functions Of Ampkmentioning
confidence: 99%
“…52 Briefly, the cells were seeded at a density of 3£10 3 , transfected with either SRPK2 siRNA or a scrambled siRNA as a control. The cells were allowed to grow for 10-12 days and the colonies were fixed with methanol, stained with 4% methylene blue and counted.…”
Section: Colony Formation Assaysmentioning
confidence: 99%
“…52 Briefly, the invasive ability of the cells was assayed using polyethylene terephthalate (PET) membrane (8-mm pore size) (Catalog # 353097, BD Biosciences). The upper compartment of the culture insert was coated with Matrigel (Catalog # 354234, BD Biosciences).…”
Section: Cell Invasion Assaysmentioning
confidence: 99%
“…13,16,17 Previous study from our group demonstrated that silencing or inhibiting CaMKK2 activity inhibited cellular proliferation, colony formation and invasive ability of gastric cancer cells. 15 In this study, we determined the role of CaMKK2 as an alternative to curcumin in HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…CaMKK2 has been reported to be elevated in gastric, prostate and hepatic cancers. [13][14][15] CaMKK2 has been shown to regulate growth, migration and progression of prostate cancer cells. 13,16,17 Previous study from our group demonstrated that silencing or inhibiting CaMKK2 activity inhibited cellular proliferation, colony formation and invasive ability of gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%